EFEKTIFITAS PENGAWET NABATI DARI TUBA (Derris Elliptica BENTH.) MELALUI EKSTRAKSI PADA TITIK DIDIH PELARUTNYA YANG DIAPLIKASIKAN PADA BEBAK GEWANG - Prabawa, Sigit Baktya (Universitas Nusa Bangsa, 2018)
In East Nusa Tenggara (NTT) area there are many Gewang trees (Corypha utan LAMK.). Many people in NTT use Gewang midrib as components of home buildings such as walls and ceilings. But the building components of the Gewang midribs contain ingredients that have the potential to be attacked by organisms such as termites. To overcome this, preservation action is needed. On the other hand there are several types of toxic forest flora that are recommended as sources of vegetable preservatives including Tuba (Derris elliptica BENTH.). Meanwhile, there has not been much research on preservation for gewang midribs. Therefore this study aims to determine the effectiveness of vegetable preservatives from Tuba for preservation of Gewang midribs through extraction at the temperature of the boiling point of the solvent. Extraction of Tuba plants was carried out using a solvent of Acetone, Methanol and Water each at the boiling point temperature for 1 hour in a ratio of 1: 8. The results showed that through GCMS analysis and preservative effectiveness testing through soil termite tests indicated that the extraction method used in this study resulted in no sufficient amount of active ingredients to be used as vegetable preservatives or able to preserve gewang midribs. The results of this study recommended that in order to obtain active ingredients from Tuba plant extracts as vegetable preservatives to preserve gewang midribs, it is not recommended to extract these plants using extraction methods as was done in this study. Instead, to obtain active ingredients from Tuba plant extracts, it is recommended to try to extract using methanol at room temperature for 72 hours in a ratio of 1: 5.